The Application Of Youtube-Based Scaffolding Learning to Improve Student Learning Outcomes in Graphic Design Subjects at SMKN 4 Barru - Inar; Muhammad Yusuf Mappeasse; Mustari S Lamada (PT. Global Research Collaboration, 2026)
Background/Context: The rapid development of digital technology necessitates the adoption of innovative instructional strategies in vocational education, particularly in practice-oriented subjects such as Graphic Design. Conventional teaching approaches often result in low student engagement and suboptimal learning outcomes, indicating the need to integrate digital media with appropriate pedagogical support to enhance the effectiveness of the learning process. Objective/Purpose: This study aims to enhance student engagement and learning outcomes through the implementation of YouTube-based instructional videos combined with a scaffolding approach in a Graphic Design course at a vocational high school. Method: This study employed a Classroom Action Research design involving Grade X students enrolled in the Computer and Network Engineering programme. The research was conducted in two cycles, each comprising the stages of planning, action, observation, and reflection. Data were collected through observations, documentation, and learning outcome tests, and were analysed using descriptive analysis. Results: The results indicate that the implementation of YouTube-based instructional videos integrated with a scaffolding approach improved the overall quality of the learning process. Student engagement and participation increased across the instructional cycles, with learners demonstrating greater independence and confidence in completing learning tasks. The approach also contributed positively to the improvement of students’ learning outcomes at the class level. Conclusion: The findings indicate that integrating YouTube-based instructional videos with a structured scaffolding approach effectively enhances student engagement and learning outcomes in Graphic Design, offering an adaptive instructional strategy for vocational education.